Growth Direction and Exposed Facets of Cu/Cu2o Nanostructures Affect Product Selectivity in co2 Electroreduction - Aguirre-Quintana, M; Aguirre-Quintana, M; Ruiz-Leon, D; Ruiz-Leon, D (Elsevier Ltd, 2022)
The electrochemical reduction of CO2 to fuels and value-added chemicals on metallic copper is an attractive strategy for valorizing CO2 emissions. However, favoring the CO2 reduction over hydrogen evolution and exclusive control of selectivity towards C1 or C2+ products by restructuring the copper surface is a major challenge. Herein, we exploit the differential orientation of the exposed facets in copper nanostructures that can tune the product selectivity in CO2 electroreduction. The Cu nanostructure with predominant {111} orientation produce C1 products only upon CO2 electroreduction at an applied potential of −1.3 V vs. reversible hydrogen electrodes (RHE), with 66.57% Faradaic efficiency (FE) for methane. Whereas the vertically grown copper nanostructures that are oriented in {110} direction have higher dislocation density and show greater CO2 electroreduction activity (>95%) at the same applied potential, with FE towards ethylene 24.39% and that of oxygenates 41.31%. FIA-DEMS analysis provided experimental evidence of selectivity of methane over methanol at higher overpotentials indicating the mechanism of methane formation occurs via *COH intermediate. The ethylene formation at a potential −1.0 V vs. RHE or more negative to it suggests a common intermediate for methane and ethylene on the vertically grown copper nanostructures. This work advances the understanding between the product selectivity and the surface structure of the copper nanostructures in electrochemical CO2 reduction. © 2021 Elsevier B.V.